Kinetics of Oxidation of L-Malic Acid by Mn(III) Pyrophosphate - Tripathi, R.S.; Gupta, R.P. (Asian Journal of Chemistry, 2010)
The oxidation of L-malic acid by Mn(III) pyrophosphate in sulphuric acid medium has been found to be first order with respect to Mn(III). The oxidation rate has been found to increase with [malic acid], [H+] decreases inversely with [pyrophosphate] free. Thermodynamic parameters have been evaluated and a suitable mechanism involving complex formation and free radicals is proposed.